FORMULASI SEDIAAN SALEP KOMBINASI EKSTRAK ETANOL DAUN NANGKA (Artocarpus heterophyllus Lam.) DAN DAUN KERSEN (Muntingia calabura L.)TERHADAP PENYEMBUHAN LUKA TERBUKA PADA TIKUS JANTAN PUTIH TAHUN 2022 - masria phetheresia sianipar (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2023)
Background: Wounds are damage to part of body tissue or damage to tissue components, where there are damaged or missing tissue substances. Jackfruit leaves (Artocarpus heterophyllus Lam.) contain secondary metabolites, namely, flavonoids, saponins and tannins. Flavonoids function as antibacterial and reduce inflammation in wounds. Saponins to trigger the formation of collagen. While the tannins function as an antibacterial. Cherry leaves (Muntingia calabura L.) contain several active compounds such as flavonoids, saponins, and tannins. Compounds that function as anti-inflammatory are flavonoids. These compounds can accelerate wound healing because it has anti-inflammatory activity. Objective: to determine the concentration of the combination ointment of jackfruit leaf and cherry leaf ethanol extract in the form of an ointment that is most effective in healing open wounds. Method : Experimentally. Samples using jackfruit and cherry leaves were taken purposively, extracted by maceration using 96% ethanol as a solvent made in the form of a thick extract. Then the thick extract was made into an ointment with a ratio of 1:2, 2:1 and 2:2 as well as positive control (bacitracin ointment), negative control (ointment base). open wound for 14 days. Results: The results of the open wound healing study had the best effectiveness, namely bacitracin ointment (0 cm), a combination ointment of jackfruit leaf and cherry ethanol extract 2:2 (0.10 cm), 1:2 (0.25 cm) and 2 :1 (0.28 cm) then ointment base (0.55 cm). Conclusion : The preparation of ointment combination of jackfruit leaf ethanol extract and 2:2 cherry is more effective in the treatment of open wounds.